Tuberculosis situation in children in 2021 and the prospects of its change in 2022 - V. A. Aksenova; S. A. Sterlikov; D. A. Kucheryavaya; A. V. Gordina; Ya. Yu. Pankova; I. A. Vasilyeva (Туберкулез и болезни лёгких)
The article analyzes changes in the epidemic tuberculosis situation in children and factors inﬂuencing it. Data from tuberculosis statistical surveillance forms and on-line monitoring data for the biggest available period were studied. It was found that in 2021, tuberculosis incidence increased in children of 0-14 years old, and this increase was statistically signiﬁcant (p < 0.05) in the group of children of 7-14years old (from 5.6 to 6.3 per 100,000 children of 7-14 years old), which may be related to the COVID-19 pandemic: increased epidemic risk of tuberculosis infection sources and increased exposure of children primarily of school age, who were switched to distant learning.The increase in tuberculosis incidence among children exposed to tuberculosis patients from 143.8 to 183.0 per 100,000 exposed children may be further attributed to decreased dissociating of contacts by hospitalizing children to tuberculosis sanatoria. Theepidemic tuberculosis situation in children is expected to deteriorate due to increased migration from the country with an unfavorable tuberculosis situation, i.e. Ukraine. Tuberculosis mortality in children continued to decline; there were no signs that it would increase in 2022.